The Reconstruction of Social Sufism Studies: Quranic Sufism as the Basis of Internalizing Social Character and Identity - Zenrif, Muchammad Fauzan; Nuqul, Fathul Lubabin; Mustofa, M. Lutfi; Barizi, Achmad Barizi (Universitas Islam Negeri Mataram, 2024)
This scholarly investigation aims to elucidate and evaluate the manifestations of social Sufism, employing the framework of Social Representation Theory (SRT) in conjunction with the Quranic context. The analysis centers on Surah Al-Ma'idah:2, which is essential for comprehending the fundamental tenets of faith and ethical considerations in Islamic discourse. Adopting a qualitative descriptive research methodology, the inquiry undertakes an empirical investigation in Malang Regency, which is distinguished for its significant contribution to the social stuff of East Java, which is characterized by a profound cultural and traditional heritage. Findings indicate that the practices of social Sufism in Malang Regency are profoundly influenced by the exegetical understanding of Quranic Surah Al-Ma'idah:2. This research enriches the existing literature on Social Sufism, mainly through the interpretive lens of the al-Qur'an, providing an in-depth examination of the variables that contribute to character development and social identity within the frameworks of social Sufism studies. Moreover, the outcomes illuminate the quintessence of reality, revealing how individual behaviors are shaped by experiences aimed at attaining happiness and their ramifications on the social attributes of the Madurese-Santri community.